2012
DOI: 10.1016/j.rinim.2012.11.001
|View full text |Cite
|
Sign up to set email alerts
|

A clinical exploratory study with itolizumab, an anti-CD6 monoclonal antibody, in patients with rheumatoid arthritis

Abstract: T cells are involved in the pathogenesis of rheumatoid arthritis (RA). CD6 is a co-stimulatory molecule, predominantly expressed on lymphocytes, that has been linked to autoreactive responses. The purpose of this study was to evaluate the safety, immunogenicity and preliminary efficacy of itolizumab, a humanized anti-CD6 monoclonal antibody, in patients with active rheumatoid arthritis. Fifteen patients were enrolled in a phase I, open-label, dose-finding study. Five cohorts of patients received a weekly antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 46 publications
7
53
0
Order By: Relevance
“…Low immunogenicity of itolizumab has been demonstrated in previous studies, 33,35 including one in RA patients but only after 6 weeks of treatment. 33 Here, we assessed the generation of antiidiotypic antibodies against itolizumab after 12 weeks of treatment in the active group (itolizumab plus MTX).…”
Section: Itolizumab Administration Did Not Induce a Measurable Antiidmentioning
confidence: 70%
See 4 more Smart Citations
“…Low immunogenicity of itolizumab has been demonstrated in previous studies, 33,35 including one in RA patients but only after 6 weeks of treatment. 33 Here, we assessed the generation of antiidiotypic antibodies against itolizumab after 12 weeks of treatment in the active group (itolizumab plus MTX).…”
Section: Itolizumab Administration Did Not Induce a Measurable Antiidmentioning
confidence: 70%
“…25,38,39 Itolizumab, an anti-CD6 mAb, has demonstrated clinical benefits, 33,40 as well as modulation of T cell proliferation and decrease of proinflammatory cytokine levels in psoriasis patients. 35 Studies have shown that itolizumab is not a T cell-depleting antibody when used as monotherapy both in Cuban RA 33 and psoriasis (unpublished data) patients. A small and transient decrease in ALC was, however, reported in an Indian study with psoriasis patients, 40 although no increase in infections was observed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations